2006
DOI: 10.1172/jci26092
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected role for angiotensin II in the link between dietary salt and proximal reabsorption

Abstract: We set out to confirm the long-held, but untested, assumption that dietary salt affects proximal reabsorption through reciprocal effects on the renin-angiotensin system in a way that facilitates salt homeostasis. Wistar rats were fed standard or high-salt diets for 7 days and then subjected to renal micropuncture for determination of single-nephron GFR (SNGFR) and proximal reabsorption. The tubuloglomerular feedback (TGF) system was used as a tool to manipulate SNGFR in order to distinguish primary changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 34 publications
8
52
0
Order By: Relevance
“…The PT is a well-characterized target of ANG II action (6,31) and NHE3 transport activity has been reported to be increased by ANG II treatment in cultured cells (9). Previous in vivo studies of the effects of ANG II infusion on PT transporters (33,38) are complicated by the fact that the ANG II infusion protocols usually raise BP (7), which is known to depress PT Na ϩ reabsorption (44), making it difficult to dissect out the effects of ANG II alone.…”
Section: Discussionmentioning
confidence: 99%
“…The PT is a well-characterized target of ANG II action (6,31) and NHE3 transport activity has been reported to be increased by ANG II treatment in cultured cells (9). Previous in vivo studies of the effects of ANG II infusion on PT transporters (33,38) are complicated by the fact that the ANG II infusion protocols usually raise BP (7), which is known to depress PT Na ϩ reabsorption (44), making it difficult to dissect out the effects of ANG II alone.…”
Section: Discussionmentioning
confidence: 99%
“…In normal subjects, GFR is either insensitive to dietary NaCl or changes in the same direction as NaCl intake (142,150). In 1995, we reported that a low-salt diet (for 7-8 days after 6 wk of diabetes) increased renal blood flow, GFR, and kidney weight in male STZ-diabetic rats (160).…”
Section: Salt Paradox In the Diabetic Kidney-link To Proximal Tubularmentioning
confidence: 99%
“…This shows a marked difference from the effect of ANG II on afferent arterioles in high renin hypertension models (22,24) and during ANG II blockade in vivo (61). ANG II increases tubular sodium reabsorption (47), although reabsorption may be decreased by ANG II in the proximal nephron (37,64). Intrarenal ANG II is important for renal function in hypertension (48) and for the proximal tubular natriuretic effect of ANG II through stimulation of AT2 receptors (29).…”
Section: Renin-angiotensinmentioning
confidence: 99%